Bridging the gap between NFT public perspectives and its Islamic finance principles - Rahmatia, Alfina; Saputra, Arief Dwi (Faculty of Economics, Universitas Islam Indonesia, 2025)
Purpose – Non-Fungible Tokens (NFT), one of the latest innovations in the financial world, have succeeded in triggering debate among the public, especially in terms of Islamic financial principles. Therefore, this study seeks to explore the gap between public societies’ perspectives on NFT on Twitter and the discourse conveyed by experts in research articles or journalists in popular articles. Methodology: This study combines two analyses, namely sentiment analysis, using the R Studio application to categorize public opinion into positive, neutral, and negative sentiments. Discourse analysis uses the NVivo 12 application to identify critical themes in scientific writing.Findings – The results show various perceptions of positive sentiments often associated with NFT and innovation. By contrast, negative sentiments focus on speculation, lack of clarity, and the potential to conflict with the principles of Islamic finance. These findings convey concerns about the speculative nature of the NFT and its compliance with Sharia law. However, some scholars argue that NFT can be structured according to Islamic ethics if proper guidelines are followed. Implications – This study contributes to bridging the gap between public perception and scholars, so that insights arise regarding NFT as perceived within the framework of Islamic finance. Originality – We believe this study is the first qualitative study to investigate public sentiment about NFT from Twitter/X and discuss it with the principles of Islamic finance.